Effective Communication Teaching Methods in Technology Transfer in Nigeria: Sweet Potato Processors Experience [Abstract only] - Stella O. Odebode (Issues in Science and Technology Librarianship)
Nigeria Agriculture is the mainstay of Nigerian economy. The welfare and the livelihood of the rural dwellers is the major concern of extension. In recent years, several efforts have been made to enhance rural development. Agricultural extension is a non-formal system of education where farmers are taught how to use new agricultural innovations to improve their economic conditions. The transfer of agricultural technological innovation is therefore essential for sustainable rural development. The choice of communication methods for extension teaching must therefore be based on the target participants, the subject matter, the steps involved in the teaching, the resources available, the teaching skills and knowledge and the teaching situations. Modern agricultural technology has contributed significantly to agricultural development. This is particularly important when it is recalled that the gap between developed and developing countries can be largely attributed to differences in the level of technological development, adaptation and transfer process. In most developed nations, there is an advanced level of technological innovations resulting in high productive capability in agriculture as well as in industry. These technologies are not often available to farmers in developing countries. Farmers find such innovations difficult to maintain even when they are appropriate to local condition. This results in low agricultural production levels that cannot sustain the rapidly increasing population and the growing demand of the people for better living standards. Furthermore, the means of disseminating agricultural information is essential for sustainable rural development. To build a self-reliant nation, effective teaching methods are essential to educate the farmers (especially women) on the use of improved technologies. Sweet potato (though not popular) is one of the important root crops in Nigeria. It serves as food at home and is useful in food industry. Sweet potato can be boiled or fried. It can be made into potato crisps, potato chips, starch, alcohol, wine, flour, "gari" and animal feed. One hundred and twenty respondents were randomly selected from 5 of the 6 geopolitical zones of Nigeria (Women In-Agriculture Unit of the ADP). Respondents were asked to answer questions based on their sources of information on transfer of sweet potato "gari" and "lafun" through the three major methods of extension communication--individual method, group method, and mass media method. Results showed that the mass media method (through a farm radio program) is contributing effectively to having sustainable rural development. A major conclusion of this paper is that the use of appropriate and effective methods or a combination of the three extension methods will enhance the promotion and development of the sweet potato industry in Nigeria.